Lipoprotein(a), remote ischemic conditioning, and stroke recurrence in patients with symptomatic intracranial atherosclerotic stenosis - Chuanjie Wu; Chengbei Hou; Wenbo Zhao; Chuanhui Li; Xuehong Chu; Longfei Wu; Yuan Wang; Chen Zhou; Guiyou Liu; Wanying Zhang; Ming Li; Zhengfei Ma; et al. (Neurotherapeutics)
This study is to determine symptomatic intracranial atherosclerotic stenosis (ICAS), a significant stroke cause with high recurrence risks, by examining the relationship between lipoprotein(a) and ischemic stroke recurrence. Analyzing data from the RICA trial (chronic remote ischemic conditioning in patients with symptomatic ICAS) involving 1286 patients aged 40–80 years across 84 Chinese stroke centers, we found that participants with lipoprotein(a) levels above 17.4 ​mg/dL experienced markedly higher stroke recurrence rates (adjusted hazard ratio [HR], 1.38; 95 ​% CI, 1.05–1.80; P ​= ​0.02), with each doubling of lipoprotein(a) increasing recurrent stroke risk by 18 ​% (adjusted HR, 1.18; 95 ​% CI, 1.09–1.29; P ​< ​0.001). Notably, among high lipoprotein(a) participants, the remote ischemic conditioning group demonstrated a lower stroke incidence (16.7 ​%) compared to the control group (22.6 ​%), suggesting potential therapeutic benefits (adjusted HR, 0.67; 95 ​% CI, 0.47–0.96; P ​= ​0.03). The study revealed that elevated lipoprotein(a) levels are independently correlated with increased recurrent ischemic stroke risk in patients with symptomatic ICAS, and those with higher lipoprotein(a) levels might derive more clinical advantages from remote ischemic conditioning. Additional research is required to validate these results.